E-099 Phenotypes of arterial calcification visualized with laser angioscopy. (23rd July 2022) - Madhani, S; Arturo Larco, J; Liu, Y; Savastano, L
Abstract : Introduction: The presence of calcifications in carotid atherosclerotic plaques has been subject to much debate with conflicting reports about their stabilizing effects. Current classifications to characterize these calcifications are limited by the use of indirect imaging modalities such as computed tomography (CT), computed tomography angiogram (CTA), magnetic resonance imaging (MRI) and ultrasound (U/S) which are suboptimal to visualize the luminal side of the vessels. Laser Angioscopy enabled by scanning fiber endoscopy (SFE) may provide an unprecedented direct visualization of the calcification phenotypes at the lumen-wall interface. Materials and Methods: After approval from the institutional review board, human cadaveric carotid artery specimens and carotid endarterectomy specimens were obtained and processed for storage and imaging. For each specimen, the common carotid artery (CCA), external carotid artery (ECA) and internal carotid artery (ICA) were imaged using a SFE (VerAvanti Inc and University of Washington). Specimens identified as having calcifications were then further imaged with Micro CT for characterization of calcified structures. Results: 120 human cadaveric carotid artery specimens and 60 carotid endarterectomy specimens were imaged. Of these, 23 specimens were shortlisted for recurrent distinguishable patterns of calcifications with SFE and imaged with Micro CT. The patterns of calcifications were divided into three major categories namely juxta-luminal, intra-luminal and mixed. Juxta-luminal calcifications were further divided into either covered, if covered by intima or exposed if not covered by non-calcified intima. Intra luminal calcifications were further divided into nodules (smooth protrusion) and coral calcifications (numerous disorganized spiculae and loosely consolidated small fragments of calcified particles). Coral calcifications could be either immobile (covered with tissue) or mobile (loosely attached to the arterial surface by thin threads of tissue). Conclusion: Laser angioscopy revealed recurrent phenotypes of intimal calcification with possible diagnostic, prognostic, and therapeutic relevance. Disclosures: S. Madhani: None. J. Arturo Larco: None. Y. Liu: None. L. Savastano: None.